Analisis Pengaruh Kualitas Pelayanan, Kepercayaan Dan Persepsi Harga Terhadap Kepuasan Pelanggan Pada CV Flobamora Logistic Di Surabaya - Kristianus Marko Talur (JURNAL RISET MANAJEMEN (JURMA), 2023)
One of the most important factors is to encourage service, namely quality, because of this quality the customer will emerge a sense of satisfaction.The purpose of this study is to analyze the effect of service quality, trust and price perceptions on customer satisfaction at CV Flobamora Logistics in Surabaya. The type of research used in this research is quantitative research, the number of respondents is 100 customers, the analysis technique used is regression analysis. multiple linear and path analysis to test the hypothesis. while the classic assumption test used is the multicollinearity test, heteroscedasticity test, autocorrelation test and data normality test. On the findings of the analysis concluded that all independent variables have a significant effect on the dependent variable.